Aplikasi Sistem Informasi Manajemen pada Usaha Peternakan (Studi Kasus: Kelompok Tani Serambi Mekah Padang Panjang) - Siska Fitrianti (Jurnal Penelitian Pertanian Terapan, 2014)
Science and technology for society have been made in Serambi Mekah farmer groups with the aim to improving the managerial capacity of the business with the help of Management Information Systems (MIS). Event starts from the identification of the Standard Operational Procedure, making the algorithm, design tables, forms, queries and reports using Microsoft Access and Microsoft Visual Basic to a SIM application software. The results showed activities SIM can be used as a controller to support the business as a business decision and record all activities in a systematic and integrated transactions. SIM can provide information to support management decisions to be taken manager, enabling better decisions can be made quickly and accurately. Support bookkeeping in SIM allows manager can easily keep an eye on corporate wealth, monitor progress and provide reports to business stakeholders. Key words : information systems, management, dairy cattle, bookkeeping